Video Editing Workshop Using Power Director Application at the Mojosongo Javanese Christian Church Surakarta - Sundari Sundari; Heribertus Ary Setyadi; Bambang Eka Purnama (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2022)
The handling of the covid-19 outbreak is carried out by all Christians in the world by carrying out virtual worship, every activity within the scope of the Javanese Christian Church  Mojosongo in particular many were suspended temporarily and some were not carried out at all. Activities such as household worship, youth worship and even Sunday Schools are also carried out in groups to achieve the goal of breaking the chain of spread of COVID-19. The church has limited multimedia equipment to support all online activities. Limited Human Resources who master multimedia and video editing in producing short videos such as MATAHARI (MAzmur kiTA HAri Ini) which must be published every day, and others. To overcome the existing problems, it is necessary to explain and train about the implementation of virtual worship and live streaming. Training is needed on the implementation of taping activities and doing video editing so that all activities can be carried out properly. For this reason, training is needed on how to tap properly and correctly and how to do video editing with the Power Director and other tools so that the congregation can enjoy it well.